Growth Hormone Gene Diversity and Quantitative Characteristics of Thin-Tailed Sheep in Muara Tembesi District Batang Hari Regency - Pratama, Bondan; Depison, Depison; Gushairiyanto, Gushairiyanto; Gunawan, Asep; Sumantri, Cece (Jurnal Ilmu-Ilmu Peternakan, 2024)
Research on thin-tailed sheep (TTS) via quantitative and molecular characterization is essential for obtaining primary data on genetic diversity. The quantitative description includes body weight, weight gain, and body measurements. Molecular characterization is performed directly on structural genes. One gene that affects livestock growth and metabolism is the growth hormone (GH) gene. The commonly used method is PCR-RFLP. The research was conducted in two stages. Field research was conducted to obtain quantitative characteristic data, including body weight, weight gain, and body measurements, as well as blood samples from 62 TTS (31 males and 31 females). Research in the laboratory includes DNA extraction, PCR amplification, and restriction with the Msp1 enzyme. Data analysis included a t test to calculate the differences in body weight, weight gain, and body size between male and female TTS. T2-hotelling was used to compare the morphometric body sizes of the male and female TTS simultaneously, and principal component analysis was used to determine the body shape and size characteristics of the male and female TTS. The results revealed that the male TTS mean body weight, weight gain, and body size were significantly (P<0.05) greater than those of the female TTS. The results of the molecular analysis of the GH gene with the MspI cutting enzyme revealed that it is monomorphic with the ++ genotype. Conclusion: Body weight, weight gain, and body size were greater in males with TTS than in females with TTS. The body size characteristics of male and female TTS patients were body length, shoulder height, and chest circumference. The body shape characteristic was chest depth. The restriction of the GH|Msp1 TTS gene DNA fragment in exon 5 in the Muara Tembesi district is monomorphic.